Study on the Dynamics Characteristic of Helical Gear with Tooth Profile Deviation - Zhang Yanjie; Wu Xuncheng; Zhang Juecheng (Jixie chuandong)
For study the impact of the tooth profile total deviation on the dynamics characteristic of helical gear,based on theoretical involute and tooth profile total deviation value,the mathematical model of error involute with tooth profile deviation is established.By taking a involute helical gear pair as the research object,the 3D model of helical gear pair with tooth profile deviation is established by using UG,and the reliability of the ideal model is verified by using ADAMS.Meanwhile,combining the ANSYS,the angular velocity,angular acceleration of driven gear of the error model and ideal model are compared and analyzed.The results show that the conclusion in dynamics simulation based on ADAMS is the nearly same as transient kinetic analysis based on ANSYS.The tooth profile deviation has significant effect on the angular velocity and angular acceleration of driven gear.